The Role of Traditional Leaders in Rote Ndao in Case Resolution through Restorative Justice - Yenny Febrianty; Roni Jayawinangun; Jonathan Rey Cusa; Rindiana Larasati (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the role of traditional leaders in Rote Ndao in resolving cases based on restorative justice and to assess the effectiveness of traditional mechanisms in realizing restorative justice at the local level. The method used in this study is a normative juridical approach supported by factual data obtained through literature study, analysis of legislation, and review of literature related to customary dispute resolution practices in Indonesia. The novelty of this research lies in the integration model between Rote Ndao customary law and the principles of restorative justice in handling minor crimes. This model shows that customary mechanisms can serve as an alternative means of case resolution that is in line with substantive justice and local values. The results of the study show that customary leaders play a strategic role as mediators and facilitators of deliberations who are able to resolve cases peacefully without going through litigation. This mechanism not only resolves conflicts but also restores social relations, strengthens community solidarity, and preserves local wisdom values. Conclusion The role of traditional leaders in Rote Ndao is highly relevant to be strengthened as part of dispute resolution policies at the local level. This approach can be used as a model for other regions in integrating customary law and positive law to achieve substantive justice and social sustainability.